Two-row adapted Motorized Weeder (AMW) for irrigated and rainfed lowland systems in sub-Saharan Africa - CGIAR Research Program on Rice (2021)
Locally adapted weeders were developed together with private fabricators and tested with farmers in 2016 and 2017. Technical drawings and specifications were completed in 2018. In 2020, AMWs are being introduced in Madagascar, Kenya and Uganda. It has been produced and shipped to many SSA countries.